2021
DOI: 10.3389/fpsyg.2021.601389
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as a Means to Well-Being in Times of COVID-19 Pandemic: Results of a Cross-Cultural Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has brought about unprecedented uncertainty and challenges to the worldwide economy and people’s everyday life. Anecdotal and scientific evidence has documented the existence of a positive relationship between the experience of crisis and creativity. Though this appears to be ubiquitous, the crisis-creativity-well-being relationship has not been sufficiently examined across countries and using a working adult sample. The current study drew on a sample consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 99 publications
(145 reference statements)
2
46
0
6
Order By: Relevance
“…That is, despite emerging adults experiencing different degrees of impact due to COVID-19, the processes they experience are the same across emerging adults in the countries we studied. Our results are in line with the study of Tang et al (2021) who found that the perceived impact of COVID-19 had the same effect on individual flourishing across different nations (the US, Germany, and China).…”
Section: Discussionsupporting
confidence: 93%
“…That is, despite emerging adults experiencing different degrees of impact due to COVID-19, the processes they experience are the same across emerging adults in the countries we studied. Our results are in line with the study of Tang et al (2021) who found that the perceived impact of COVID-19 had the same effect on individual flourishing across different nations (the US, Germany, and China).…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, very recent studies have shown that creativity acts as a mitigating factor of the detrimental effects of COVID‐19 restrictions on wellbeing (Tang et al, 2021 ; Ying et al, 2020 ) in healthy subjects. Considering these findings and the tight relationship between creativity and narcolepsy, in the present study we aimed at exploring whether NT1 patients’ creative abilities could affect patients’ wellbeing during the first Italian generalised lockdown (in the period starting from March 10 until May 17, 2020; Government of Italy, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings imply that Chinese enterprises should consider new strategies to manage cross-culture conflicts, especially during the COVID-19 pandemic (Tang et al, 2021). First, the management of the enterprises values the importance of learning Confucian culture.…”
Section: Discussionmentioning
confidence: 83%